Evaluating the functional efficacy of an aqua-based silver fluoride solution - Dr Mahdi Shahmoradi; Professor Qing Li; Professor Michael Swain (Elsevier, 2023)
Aim or Purpose: The purpose of this study was to investigate the functional efficacy of an aqua-based silver fluoride solution in comparison with an ammonia-based silver fluoride solution for the treatment of carious enamel lesions. Materials and Methods: Computed tomography was employed to explore the diffusion and interaction of silver fluoride solutions with sound and carious enamel. X-Ray Diffraction (XRD) analysis was performed using XPERT Pro Diffractometer to understand the interaction products of silver diamine fluoride and aqueous silver fluoride with sound and carious enamel crystals. Field-emission SEM was used to view the morphology of the formed phases. Results: MicroCT results showed that both silver fluoride solutions significantly penetrate within caries micro-cavitations and presented significant wettability and retention in the occlusal fissures. Non-cavitated enamel surface (either sound or carious) showed to prevent the ingress of Ammonia or aqua based solutions into the subsurface area of the enamel irrespective of the size and depth of the lesion. The results of XRD indicated the formation of new peaks and new phases on the silver fluoride treated enamel surface corresponding to fluorapatite and calcium fluoride compositions. FE-SEM image of AgF treated enamel, showed the homogenous distribution of AgF related particles along the enamel crystals of rod and interrod regions. Conclusions: Aqua-based silver fluoride exhibited similar functional efficacy in terms of penetration, phase formation and particle distribution when compared to ammonia-based solution. The significant diffusion of both silver fluoride solutions within micro-cavitations and in the occlusal fissures provides an excellent means for eradicating and protecting against the bacterial biofilm within these inaccessible areas of the tooth.